The time course of aggressive behaviour in juvenile matrinxa Brycon amazonicus fed with dietary L-tryptophan supplementation - Wolkers, C. P. B. [UNESP]; Serra, M. [UNESP]; Szawka, R. E.; Urbinati, E. C. [UNESP] (Wiley-Blackwell, 2014)
This study evaluated the influence of dietary L-tryptophan (TRP) supplementation on the time course of aggressive behaviour and on neuroendocrine and hormonal indicators in juvenile matrinxA Brycon amazonicus. Supplementation with TRP promoted a change in the fight pattern at the beginning of an interaction with an intruder, resulting in decreased aggressive behaviours during the first 20min. The decrease in aggression did not persist throughout the interaction but increased at 3 and 6h after the beginning of the fight. Monoamine levels in the hypothalamus were not influenced by TRP before or after the fight; however, the hypothalamic serotonin (5-HT) concentration and the 5-hydroxyindole-3-acetic acid (5HIAA):5-HT ratio were significantly correlated with the reduction in aggressive behaviour at the beginning of the fight. Cortisol was not altered by TRP before the fight. After the fight cortisol increased to higher levels in B. amazonicus fed with supplementary TRP. These results indicate that TRP supplementation alters the aggressive behaviour of B. amazonicus and that this effect is limited to the beginning of the fight, suggesting a transient effect of TRP on aggressive behaviour. This is the first study reporting the effects of TRP supplementation on the time course of aggressive interaction in fishes. (C) 2013 The Fisheries Society of the British Isles
Keywords: Aggressiveness; Cortisol; Serotonin; Social stress